The National Image of China in Cuban Reports on COVID-19 Pandemic: A Study Based on the Linguistic Corpus and Critical Discourse Analysis - Zhi, Chen; Haowen, Cai (Sinología hispánica. China Studies Review, 2024)
Based on Fairclough’s Three-Dimensional Model of Discourse, the present work aims to investigate the national image of China created by Cuba’s three main media outlets related to the pandemic in China, which are Granma, Juventud Rebelde and Trabajadores. Through textual, discourse and social analysis, the study shows that the news reports on the pandemic in China, from all three Cuban media outlets, are positive and present China as a responsible nation that can provide help to others in difficult times and promote cooperation between countries to build a Community of Common Destiny worldwide.